HUBUNGAN DUKUNGAN SUAMI DENGAN KETEPATAN ANTENATAL CARE DI DESA BAGI KABUPATEN MADIUN - Sari, Rury Narulita; Kusparlina, Eny Pemilu (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Correlation of the husband support and the accuracy of antenatal care in Desa Bagi Kabupaten Madiun. Antenatal care (ANC) is preventive efforts of obstetric health programs for output optimization of maternal and neonatal through series of activities routine monitoring of pregnancy. Support husband has big hand in maternal health status during pregnancy, labor, until her chilbirth. This research objective is to know the extent of the supprt husband against his wife’s pregnancy in making a visit ANC so hopefully pregnant women can make a visit antenatal care routinely. The research type was an observational analytic with cross sectional approach. The research population was a 3rd trimester pregnant women in Desa Bagi Kabupaten Madiun, samples taken by simple random sampling as many as 41 people. With the data collection techniques was using questionnaire and item statement 12 question and documentation study results of book ANC’s visit. Data analyzing was using the uji chi square with dk=1, Ho rejected if X2 count > X2 table with α = 0,05 (3,841). The result of the research is there is a significant correlation of the husband support to the timeliness of the visit schedule antenatal care in pregnant women trimester III in Desa Bagi Kecamatan/ Kabupaten Madiun.Keywords : support husband, pregnancy, antenatal car